Funções porosidades e velocidades no movimento gravitacional de uma suspensão particulada em proveta - Mendes, Hariel Udi Santana (2019)
The study of the gravitational movement of a particulate suspension is of great importance for the establishment of phenomenological parameters of the process and for the prediction of parameter values necessary for the calculations of sedimentation projects and the sedimentation of solid particles present in drilling fluids and completion of oil wells. In this work, based on the beakers’ testsfor the gravitational movement, we consider the regions of free sedimentation, transition and compaction, occupied by the suspension during the process. The suspension in the beaker was modeled by a porous medium with restriction of incompressibility that, under certain conditions, allows the establishment of equations for the porosities and velocities functions in these three regions. In the equations that directly provide the porosities functions for the transition and compaction regions, there are constant parameters that need to be determined, which also appear in the equations describing the height of the upper descending interface, the accelerating wave, and the lower ascending interface. The equations proposed for the height of the upper descending interface showed a good fit in relation to the experimental data of the barite, calcite and atapulgite particulate suspensions test with known initial porosity. For the lower ascending interface, the behavior is consistent with literature forms. The numerical results for porosities and velocities are in accordance with literature results, that is, they tend to increase, in module, from the bottom of the beaker to the height of the upper descending interface and decrease with time in each position.